A study on changes in meaning in literary translation - Tabligan, Mitzel A. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1992)
This is a study on changes in meaning in literary translation. This thesis tried to go into an analysis on the changes in meaning in Dr. Jose Villa Panganiban's translation of William Shakespeare's play, Julius Caesar. This study shows that translation always brings about changes in meaning in the translated text since English and tagalog are two distinct languages. English has unique features which are difficult to fully render into tagalog. The difference in culture leads to over translation, under translation and lack of equivalence. The author and the translator have different use of language, and style in writing. They may attach private meanings to words. Moreover, they have different theories of meaning and values. This study also shows the qualities that our Filipino translator must possess in translating literary texts especially Shakespearian plays. The writer hopes that this study will benefit our Filipino translator.
Thesis (Bachelor of Arts)
Keywords: Translating and interpreting